Analisis Penerapan Balance Scorecard, Alat Ukur Penilaian Kinerja pada Dinas Pendapatan, Pengelolaan Keuangan, dan Aset Kabupaten Sidoarjo - Mahsina Mahsina; Asmie Poniwatie; Cholifah Cholifah (Jurnal Maksipreneur, 2017)
Nowadays, the performance measurement is often only measure of financial performance, and it cannot portray overall the company’s performance. It’s given these shortcomings, then created a performance measurement method that considers the financial aspects as known as the Balanced Scorecard. Balanced Scorecard performance measurement involves four perspectives: i.e. financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. The authors choose to use Dinas Pendapatan, Pengelolaan Keuangan, dan Aset of Sidoarjo Regional Government Agency, because during the measurement of performance of company remains focused on financial aspects. The approach of this study is a qualitative approach. The data source are secondary data, where it is an overview of the company gained from those authorized in the agency, vision, mission, strategy, and corporate organization sectors. The research result of this study using the balanced scorecard performance that involves the four perspectives.